Post-Trial Feedback Alters Landing Performance in Adolescent Female Athletes Using a Portable Feedback System - Thomas W Kernozek; Drew Rutherford; Becky Heinert; Jessica Onsager; Maria Lee; Jeremie Schiedermayer; Stephanie Dietrich; Renee Dade; Thomas Gus Almonroeder (North American Sports Medicine Institute, 2021)
# Background Post-performance verbal and visual feedback based on data collected via lab-based instruments have been shown to improve landing patterns related to non-contact ACL injury. Biomechanical methods are often complex, difficult to transport and utilize in field settings, and costly, which limits their use for injury prevention. Developing systems that can readily provide feedback outside of the lab setting may support large scale use of feedback training for ACL injury prevention. # Purpose/Hypothesis The purpose of this study was to investigate the effectiveness of a single training session using a custom portable feedback training system that provides performance cues to promote changes in impact kinetics and lower extremity position during landing in female athletes. # Study Design Repeated measures # Methods One hundred fifty female athletes (ages 13-18 years old) landed from a 50 cm platform with and without feedback related to vertical ground reaction force (vGRF), vGRF symmetry and lower extremity position. Feedback was provided via a portable, low-cost system that included two custom-built force plates interfaced with a digital camera. Each athlete performed six pre-test trials followed by two blocks of six trials where they received visual feedback from the training system and individualized verbal cues from an investigator. Following training blocks, athletes completed six post-test trials without feedback and then six dual-task trials where a ball was randomly thrown to the performer during the landing (transfer task). vGRF and knee to ankle (K:A) separation ratio were measured and the average responses were reported for each trial block. # Results Differences in vGRF between baseline, post-test and transfer task trial blocks were observed (F(2,298)=181.68, p < .0001). Mean (SD) peak vGRF (body weight) were 4.43 (0.90), 3.28 (0.61), and 3.80 (0.92), respectively. Differences in K:A ratio between baseline, post-test and transfer task trial blocks were shown (F(2,298)=68.47, p < .0001). Mean (SD) K:A ratio were 0.87 (0.21), 0.98 (0.19), and 0.92 (0.19), respectively. # Conclusion A portable feedback system may be effective in reducing peak vGRFs and promoting a more desirable K:A ratio during landing and transfer task landing in adolescent female athletes. # Level of Evidence 3b